David Jasper, The Sacred Desert: Religion, Literature, Art, and Culture - Wainwright, Andy (Journal for the study of religion, nature and culture, 2006)
David Jasper, The Sacred Desert: Religion, Literature, Art, and Culture (Malden, MA and Oxford: Blackwell Publishing, 2004), pp. xix + 208. Paperback $25. ISBN 1-4051-1975-6. Hardback $58. 1-4051-1974-8.